THE ROLE OF PHYSICS IN STUDENTS’ NATURE CONSERVATION - Eshtuxtarova, Orzigul (Физико-технологического образование, 2024)
In this work we show that in order to prevent the negative consequences of human penetration and intervention in nature, it is necessary to solve a number of scientific-technical, socio-political, economic and other problems, among which the issue of environmental education and upbringing of the young generation is the most important. It has been considered that the growing young generation should be ready to take a careful approach to the natural environment that surrounds us from the threshold of school and a scientific approach